EFEKTIFITAS PENYEDERHANAAN PROSEDUR PENDAFTARAN KEKAYAAN INTELEKTUAL DALAM UU CIPTA KERJA UNTUK MENDORONG INOVASI UMKM - Surya Insani Kamil (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia’s economy, contributing significantly to the national Gross Domestic Product (GDP) and absorbing a large portion of the workforce. However, MSMEs face various challenges, especially in terms of innovation protection and intellectual property (IP) registration. Many MSMEs lack awareness about the importance of registering their intellectual property, leaving their innovative products and ideas vulnerable to plagiarism and misuse. The complexity, high costs, and lengthy procedures associated with IP registration have further hindered MSMEs from obtaining the protection they need. The enactment of the Omnibus Law (Law No. 11 of 2020) aimed to simplify administrative procedures, including those for IP registration. This study evaluates the effectiveness of this simplification, particularly its impact on MSME participation in IP registration and the protection of their innovations. The research reviews the literature on the legal, policy, and economic dimensions of IP in the MSME sector, and analyzes how the law's implementation may foster innovation and competitiveness among MSMEs. The results highlight the potential benefits and remaining challenges of IP protection in supporting MSME growth and innovation in Indonesia.